2011
DOI: 10.2466/04.10.24.pms.113.5.439-453
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Visual Realism in Drawings of Animate and Inanimate Objects

Abstract: Sex differences in a visually realistic drawing style were examined using the model of a curvy cup as an inanimate object, and the Draw-A-Person test (DAP) as a task involving animate objects, with 7-to 12-year-old children (N = 60; 30 boys). Accurately drawing the internal detail of the cup-indicating interest in a depth feature-was not dependent on age in boys, but only in girls, as 7-year-old boys were already engaging with this cup feature. However, the age effect of the correct omission of an occluded han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 58 publications
0
27
1
Order By: Relevance
“…The female advantage in the human figure drawing test is well known since Goodenough (Goodenough, 1926;Goodenough & Harris, 1950;Lange-Küttner et al, 2002;Willcock et al, 2011). Girls also drew plenty of detail when they were copying cubes that had a regular surface pattern, whereas boys focused more on the silhouette (Lange-Küttner, 2011;Lange-Küttner & Ebersbach, 2013). However, Naglieri (1988) did not provide separate standardized scores for girls and boys because, unlike Goodenough and Harris, he did not obtain significant gender differences in a large survey sample of 2,622.…”
Section: Apa Nlmmentioning
confidence: 99%
“…The female advantage in the human figure drawing test is well known since Goodenough (Goodenough, 1926;Goodenough & Harris, 1950;Lange-Küttner et al, 2002;Willcock et al, 2011). Girls also drew plenty of detail when they were copying cubes that had a regular surface pattern, whereas boys focused more on the silhouette (Lange-Küttner, 2011;Lange-Küttner & Ebersbach, 2013). However, Naglieri (1988) did not provide separate standardized scores for girls and boys because, unlike Goodenough and Harris, he did not obtain significant gender differences in a large survey sample of 2,622.…”
Section: Apa Nlmmentioning
confidence: 99%
“…However, these graphic objects are iconic and generally convey valuable disambiguating information that shows children's knowledge about object identity and function (intellectual realism) (Luquet, 1927(Luquet, /2001. For instance, a cup would always be drawn with a handle even if the handle was out of sight because this is what differentiates a cup from, for instance, a vase (Davis, 1983(Davis, , 1985Ford & Rees, 2008;Lange-Küttner, 2011). Children would even agree that a change in this kind of iconic object can have an effect on the real object (Jolley, 2008), which may have been a "leftover" from an earlier time when infants actually grasped objects in pictures (DeLoache, Pierroutsakos, Uttal, Rosengren, & Gottlieb, 1998).…”
Section: Spatial Drawing Systemsmentioning
confidence: 99%
“…However, so far it has not been shown that children at age seven know that spatial axes will converge towards the viewpoint [26]. Instead, children at this age think more about object identity and less about appearances [2,15,29,30]. Hence, it is concluded that the perspective model with the built-in perspective fits with children's belief that a picture should represent enduring properties of this world and not just an incidental subjective view such that perspective affords.…”
Section: Object-and View-specificity In Agreement: the Case Of Embodimentioning
confidence: 57%
“…Especially boys focus on the contour of figure silhouette [3,15]. However, an object contour is not a useful visual cue for drawing in perspective.…”
Section: Introductionmentioning
confidence: 99%